Human Milk Oligosaccharide Concentrations Are Associated with Multiple Fixed and Modifiable Maternal Characteristics, Environmental Factors, and Feeding Practices - Azad, Meghan B; Robertson, Bianca; Atakora, Faisal; Becker, Allan B; Subbarao, Padmaja; Moraes, Theo J; Mandhane, Piushkumar J; Turvey, Stuart E; Lefebvre, Diana L; Sears, Malcolm R; Bode, Lars (The Journal of nutrition, 2018)
Human milk oligosaccharides (HMOs) shape the developing gut microbiome and influence immune function. Aside from genetic Secretor status, the factors influencing HMO synthesis and secretion are largely unknown. We aimed to identify modifiable and nonmodifiable factors associated with HMO concentrations. This prospective observational study included a representative subset of 427 mothers participating in the CHILD birth cohort (mean age: 33 y, 73% Caucasian). Breast milk was collected at 3-4 mo postpartum. Concentrations of 19 predominant HMOs were measured by rapid high-throughput HPLC. Secretor status was defined by the presence of 2'-fucosylactose. Associations with maternal, infant, and environmental factors were explored using multivariable regression. Breastfeeding duration was explored as a secondary outcome. Overall, 72% of mothers were Secretors and the mean ± SD duration of any breastfeeding was 12.8 ± 5.7 mo. HMO profiles were highly variable; total HMO concentrations varied 3.7-fold and individual HMOs varied 20- to >100-fold. Secretor mothers had higher total HMO concentrations than did non-Secretors (mean: 15.91 ± 2.80 compared with 8.94 ± 1.51 μmol/mL, P < 0.001) and all individual HMOs differed by Secretor status, except for disialyllacto-N-tetraose (DSLNT). Most HMO concentrations were lower in milk collected later in lactation, although some were higher including DSLNT and 3'-sialyllactose. Independent of Secretor status and lactation stage, seasonal and geographic variation was observed for several HMOs. Parity, ethnicity, and breastfeeding exclusivity also emerged as independent factors associated with some HMOs, whereas diet quality and mode of delivery did not. Together, these factors explained between 14% (for 6'-sialyllactose) and 92% (for 2'-fucosyllactose) of the observed variation in HMO concentrations. Lower concentrations of lacto-N-hexaose or fucodisialyllacto-N-hexaose were associated with earlier breastfeeding cessation. HMO concentrations vary widely between mothers and are associated with multiple characteristics beyond genetic Secretor status, as well as feeding practices and environmental factors. Further research is warranted to determine how these associations affect infant health. This study was registered at clinicaltrials.gov as NCT03225534.